ٹرانس جینڈر ایکٹ 2018ء :مغربی اور اسلامی نظریات کے تناظر میں: ایک تنقیدی جائزہ : Transgender Act 2018: In the Context of Western and Islamic Ideologies: A Critical Review - Hafiz Muhammad Sohaib Ashraf; Muhammad Dawood Jamal; Naseer Ahmad (Al Manhal Research Journal, 2025)
Gender theories got a great acceptance in modern world. Gender differences and proportions are very important for societies. But like all the theories, gender theories faced criticism as well as acceptance. In these days, some laws have been made in support of gender freedom. These laws are supposed to affect people in either ways: positive or negative. This article critically examines Pakistan's Transgender Persons (Protection of Rights) Act of 2018 from both Islamic and modern Western perspectives. The analysis highlights the act's underlying Western liberal influences, arguing that it misrepresents the local "khawaja sara" community by conflating them with the Western concept of "transgender." It explains key terms like Gender Identity, Gender Expression, Sex, and Sexual Orientation and contrasts the Western multi-gender theory with the Islamic and biological two-gender binary. The article argues that the act’s provisions, particularly those allowing individuals to change their gender based on personal "feeling" rather than biological reality, are in direct conflict with Islamic law concerning inheritance, modesty (Purdah), and the sanctity of the family unit. It posits that the law could lead to widespread moral and social decay, promoting homosexuality and undermining the Islamic concept of family based on the union of a man and a woman. The text concludes with a call for intellectual and scholarly discourse, stressing the need to educate the youth on Islamic principles to counter the ideological and moral confusion stemming from Western liberal ideologies.